2022
DOI: 10.3389/fpsyg.2021.830402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EFL Teachers' Optimism and Commitment in Their Work Engagement: A Theoretical Review

Abstract: Teachers' emotional states such as optimism and commitment have long been approved influential in second/foreign language education. Although many correlational investigations have been conducted on teacher optimism and commitment, their interaction and kinship with teachers' work engagement have been largely ignored in the literature. Considering this situation, the present mini-review aims to present the theoretical underpinnings, definitions, dimensions, and conceptualizations of these three important varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
(44 reference statements)
1
26
0
Order By: Relevance
“…This is confirmed by Liu (2019) , who revealed that occupational self-efficacy was directly associated with organizational commitment and indirectly with work engagement via the mediating role of organizational commitment. Moreover, Dong and Xu’s (2022) review showed that EFL teachers’ commitment can reflect in their occupational engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by Liu (2019) , who revealed that occupational self-efficacy was directly associated with organizational commitment and indirectly with work engagement via the mediating role of organizational commitment. Moreover, Dong and Xu’s (2022) review showed that EFL teachers’ commitment can reflect in their occupational engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significance of emotional wellbeing as well as the burgeoning of positive psychology both in the field of psychology (e.g., Seligman and Csikszentmihalyi, 2000 ; Fredrickson, 2009 ) and FL education ( MacIntyre and Gregersen, 2012 ; Dewaele et al, 2019a ; Fathi and Mohammaddokht, 2021 ; Wang et al, 2021 ; Derakhshan et al, 2022 ), research has witnessed a surge of interest in teachers’ positive emotions ( Cowie, 2011 ; Khajavy, 2021 ). Hence, there has been an outstanding shift from exploring negative variables, including teacher stress ( Fathi and Derakhshan, 2019 ) and burnout ( Safari, 2021 ) to examining positive factors such as work engagement ( Dong and Xu, 2022 ), enjoyment ( Ergün and Dewaele, 2021 ), emotion regulation ( Fathi et al, 2021a ), psychological well-being ( Greenier et al, 2021 ), resilience ( Ayoobiyan and Rashidi, 2021 ), and job satisfaction ( Safari, 2021 ) and other emotion variables ( Cowie, 2011 ; Khajavy et al, 2018 ) in FL contexts. According to Boudreau et al (2018) , FL enjoyment (FLE) as a positive emotion has sparked many researchers’ keen interest in recent years ( Dewaele and Li, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of optimism is a psycho-emotional construct that took its roots in Bandura's social intellectual hypothesis, but boomed in positive psychology as a novel trend in educational psychology (Dong and Xu, 2022). It is regarded as a propensity to expect positive outcomes (Srivastava and Angelo, 2009).…”
Section: Optimism: Definitions and Dimensionsmentioning
confidence: 99%
“…By definition, optimism is one's positive expectation about the future in spite of the existing difficulties and setbacks (Carver and Scheier, 2002). It is a personal tendency to consider that one will experience good occasions in life and survive bad outcomes (Dong and Xu, 2022). In teaching, optimism means teachers' positive view about his/her ability to generate academic success among students despite challenges (Pathak and Lata, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation